'"It's sport, why does it matter?"' Professional coaches' perceptions of equity training. Issue 2 (3rd July 2018) - Norman, Leanne
Abstract: The purpose of this study was to stimulate debate as to the current value and form of equity training for UK coaches and how it impacts coaching practice. Adopting a critical feminist lens, the discussions are based on in-depth interviews with four coaches who had recently attended the 'Equity in your Coaching' workshop run by Sports Coach UK. Data analysis yielded four pertinent themes related to: coaches' language; the impact of the course on becoming a reflective practitioner; the format of the workshop; and the minimal impact on coaching practice. Through undergoing this training, coaches understood the value and worth of such education. However, in its current form, the workshop was experienced as irrelevant and too removed from practice to be of worth to these coaches. The findings illustrate the need for coach developers to more adequately understand the complexities and intricacies inherent within the coaching context.